Influence of energy and wavelength on femtosecond laser-induced nucleation of protein - Murai, Ryota; Yoshikawa, Hiroshi; Hasenaka, Hitoshi; Takahashi, Yoshinori; Maruyama, Mihoko; Sugiyama, Shigeru; Adachi, Hiroaki; Takano, Kazufumi; Matsumura, Hiroyoshi; Murakami, Satoshi; Inoue, Tsuyoshi; Mori, Yusuke (Chemical physics letters, 2011)
The influence of energy and wavelength on femtosecond laser-induced nucleation of protein was systematically investigated with Hen Egg White Lysozyme and Glucose Isomerase at two different wavelengths, λ=780nm and 260nm. We found that the enhancement of nucleation probability at a laser wavelength of λ=780nm was comparable with that at λ=260nm, which produces more protein dimers. The nucleation was dependent on laser pulse energy and could be induced beyond the threshold energy of cavitation bubbles. These results indicate that the photophysical processes like cavitation bubbles formation are main triggers for the femtosecond laser-induced nucleation.